Variations in Articulatory Movement With Changes in Speech Task. - Tasko, Stephen M.; McClean, Michael D. (Journal of Speech, Language & Hearing Research, 2004)
Studies of normal and disordered articulatory movement often rely on the use of short, simple speech tasks. However, the severity of speech disorders can be observed to vary markedly with task. Understanding task-related variations in articulatory kinematic behavior may allow for an improved understanding of normal and disordered speech motor behavior in varying communication contexts. This study evaluated how orofacial kinematic behavior varies as a function of speaking task in a group of 15 healthy male speakers. The speech tasks included a nonsense phrase with a high frequency of stop consonants, a sentence, an oral reading passage, and a spontaneous monologue. In addition, rate and intensity conditions were varied for the nonsense phrase and sentence. The articulatory positions of the upper lip, lower lip, tongue blade, and mandible were recorded, and measures reflecting (a) average features of individual movements or strokes (i.e., peak speed, distance, and duration) and (b) overall spatial variability of the articulators for each task were extracted, derived, and analyzed. Results showed a number of task- and condition-related differences in speech kinematic behavior. The most prominent result from the task comparison was that the nonsense speech task exhibited larger, faster, and longer movement strokes than the other speech tasks. For some articulators (lower lip and tongue), there were task-related differences in spatial variability. Changes in loudness and rate revealed variation in kinematic measures that were often complicated by articulator identity and task type. The results suggest that an expanded range of speech tasks and conditions may aid in the study of normal and disordered speech motor behavior. Reprinted by permission of the publisher.